Efficient light trapping via nanostructures integration in thin film organic and inorganic solar cells - Al-Menabawy, Sara Magdi (AUC Knowledge Fountain, 2018)
Solar cells provide a valuable mean to convert sunlight photons into useful electrical energy. Silicon is the most widely used material in solar cell's industry. Bulk crystalline silicon solar cells, the first solar cell generation, are currently the most widely spread type of solar cell. Although this type of solar cell provides high efficiencies, it requires high cost due to high material usage in addition to high cost of the complex fabrication techniques used. Motivated by the urgent need to develop affordable solar cells in order to be able to compete with current conventional energy sources, thin film solar cells are gaining a huge interest. Thin film solar cells are not only interesting due to the less material usage and thus the lower cost, but also because it enables the use of low-cost materials with less quality such as amorphous silicon and conductive polymers. Amorphous silicon and conductive polymers are two examples of semiconductor materials that have good optical absorption properties and could be fabricated with low cost and simple fabrication techniques. However, they suffer from poor electronic properties due the randomness of their structure causing electrons to have low diffusion length and thus, recombine fast. Light trapping techniques are the most effective way to increase the optical absorption without increasing the physical thickness of the absorbing layer. Hence, it enables the use of materials with lower quality and bulk crystalline silicon with maintaining comparable efficiencies. The use of plasmonics for light trapping in organic solar cells has been widely investigated and novel designs are still developing. However, all organic plasmonic solar cells reported are developed using metals. Here, we suggest, for the first time, the use of refractory plasmonics such as titanium nitride and zirconium nitride instead of metals in organic solar cells. Refractory plasmonics provide indispensable advantages such as their lower cost, C-MOS compatibility, higher thermal stability and wider resonance response. Several structures are numerically studied and compared. A thorough study for the scattering and absorption of these refractory plasmonics in a polymer environment is implemented. Amorphous silicon is another material that suffer from low absorption. Its high refractive index causes a huge amount of light to be reflected from its surface. In addition, its small thickness causes further photons to be transmitted without getting absorbed. Thus, the developing of several 2D and 3D surface texturing is widely investigated in literature, Here, we develop a novel fabrication technique to fabricated nanocones and nanowires from an amorphous silicon thin film with one step techniques using excimer laser. The technique suggested here is fast, simple and easily scalable. In addition, we numerically developed a double light trapping scheme for amorphous silicon solar cells that not only decrease the reflection due to addition of surface texturing, but also decrease the light transmitted due to addition of metal gratings at the back electrode. This design provides an efficient light trapping scheme that sandwiches the a-Si layer between xv two light trapping configurations resulting in huge enhancement in absorption. Another factor increasing the cost of commercially available silicon solar cells is the complex fabrication of a p-n junction. Thus hybrid solar cells that combine silicon with a polymer provide an efficient mean to easily fabricate solar cell devices. Nanostructuring the inorganic material in hybrid solar cells plays an important role in increasing the efficiency of such devices because it provides a larger interfacial area between the organic and inorganic material resulting in the dissociation pf a larger number of excitons. Here, we propose a structure based on silicon tapered nanowires coated with a low bandgap polymer. The use of tapered silicon nanowires is chosen because of the high capabilities of this structure to trap and absorb light efficiently. In addition, the choice of the low band gap polymer is thoroughly studied and several polymers are compared. The choice of the polymer was made with the aim to increase the absorption range of both materials to absorb the largest number of incident photons. This structure provides an almost unity absorption throughout the whole visible and near infra-red range with only 5 Î¼m length tapered silicon nanowires coated with 50 nm of the low band gap polymer, this design significantly reduce the amount of materials used to achieve this high absorption. All these designs are thoroughly analyzed in this thesis along with recommended fabrication techniques for numerically proposed structures. All simulations developed in this thesis were implemented using a 3D finite difference time domain (FDTD) tool (i.e. Lumerical).